Faktor-Faktor yang Mempengaruhi Perubahan Lahan Kawasan Perumahan Menjadi Kawasan Perdagangan dan Jasa - Muhammad Ramadhan; Achmad Saeful Fasa (Jurnal Konstruksi, 2024)
Limited land and high land prices in areas designated for commercial activities in the city center have resulted in the invasion of commercial functions into residential areas, one of which is the area around housing in Cibodas Baru Village. The aim of this study is to identify the factors that cause changes in residential land use to trade and commercial services in Cibodas Baru Village Housing, Cibodas District, Tangerang City. The trade and services population is 621 using the Slovin formula sampling method. The analysis method used is descriptive quantitative and superimpose (overlay), based on drone observations of existing land use in 2021 with the suitability of the Tangerang City Regional Spatial Plan for 2012-2032, there is a difference between housing and trade and services of 56,919.33 m2 (5 .65 Ha) or 9.27%. The trend of land change from 1998 to 2023 means the change per year is 0.44% per year. Analysis of factors changing residential land use to trade and services in Cibodas Baru Housing using SPSS software by entering several variables, the variable is the degree of land accessibility with a significant relationship accepted with an Asymptotic Significance (2-sided) value of 0.000004 < 0.05 then there is a strong relationship with chi-square = 21.190, therefore the higher the land accessibility, the higher the change in the function of residential land use.